Solve for y -3(y-z)=-3

Math
-3(y-z)=-3
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3(y-z)=-3 by -3.
-3(y-z)-3=-3-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3(y-z)-3=-3-3
Divide y-z by 1.
y-z=-3-3
y-z=-3-3
Divide -3 by -3.
y-z=1
y-z=1
Add z to both sides of the equation.
y=1+z
Solve for y -3(y-z)=-3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top